Analysis of the behaviour large headed stud in terms of shear resistance and failure mode using abaqus - Teh, Kai Yao (2016)
Headed stud are quite popular type of shear connector that is often used in composite structure. Shear connectors were used to resist longitudinal shear forces on the surfaces between steel and concrete. An accurate non-linear finite element model of the push-out test has been developed to investigate the capacity of large stud shear connectors (25mm and above) and the failure mode. The main objective of this study is to discover the effect of changes in stud diameter affect the shear resistance and the failure model on headed stud. There were four model in this analysis which designated as PT 1, PT 2, PT 3, PT 4 and PT 5 with stud diameter size 22mm, 25mm, 27mm, 29mm and 30mm respectively. The load per stud for PT 1, PT 2, PT 3, PT 4 and PT 5 were 103.57kN, 133.08kN, 162.47kN, 195.07kN and 226.44kN respectively. Based on the FEA result, the larger size stud diameter, will produce higher shear resistance. The stress distribution of the model is shown in the failure mode of shear stud and it is located at the weld toes of the in the horizontal direction for the top row of headed stud.